Mastering Veeam backup & replication : design and deploy a secure and resilient Veeam 12 platform using best practices - Childerhose, Chris (Packt Publishing Ltd., 2023)
Veeam is one of the leading modern data protection solutions, making it a necessary skill for anyone responsible for backing up virtual environments. This new edition of Mastering Veeam Backup & Replication is revised and updated to cover Veeam version 12. This edition covers some new features added to the application, such as VeeaMover, Per Machine Backup chains, and MFA on the console. The book guides you through implementing modern data protection solutions for your cloud and virtual infrastructure with Veeam while helping you master advanced concepts such as Continuous Data Protection (CDP), extended object storage support, VeeaMover, and security settings. You'll dive deep into other new features as well, such as Direct to Object storage, Object to Tape and learn about CDP from a service provider perspective with Veeam Cloud Connect (VCC). By the end of this Veeam book, you'll be able to successfully implement Veeam Backup & Replication to secure your environment and enable disaster recovery.